Contributions of the nurse's clinical practice to Primary Care - Carolina Kahl; Betina Horner Schlindwein Meirelles; Kamylla Santos da Cunha; Mariana da Silva Bernardo; Alacoque Lorenzini Erdmann (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To understand the repercussions of the nurse's clinical practice on Primary Health Care. Method: Qualitative research with the theoretical and methodological contribution of Grounded Theory. Data collection took place between May and October 2016 in Florianópolis' Primary Care service. The theoretical sample was comprised of 18 nurses divided into two groups. Results: nurses' clinical practice has repercussions on the consolidation of the trust bond between individuals, families and communities, by amplifying the problem-solving efficacy of the Primary Health Care professional's clinical practice. This is due to the implementation of clinical nursing protocols, and also the use of the International Classification for Nursing Practice. Final considerations: Nurses' clinical practice has positive repercussions on the health of Primary Health Care users.